2019
DOI: 10.29333/ojcmt/6428
|View full text |Cite
|
Sign up to set email alerts
|

Generations X, Y, Z and their Perception of E-Government Services: Case of Turkey

Abstract: Technological developments have transformed the forms of communication that can have a major impact on the social structure. All these technological developments cause fundamental changes in the way of life of the individuals and there are serious changes in both the ways of interpreting life and personality structures. The primary aim of this study is to examine the perceptions of online government services amongst different generations. The research of this study was carried out on the perception of e-govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Faculty student communication helps create an online community for sharing ideas and engaging in learning. 24 It is obvious that students who have better online self-efficacy feel relatively comfortable expressing themselves in writing. 43 It has been reported that misinterpreted text communication is common in online learning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Faculty student communication helps create an online community for sharing ideas and engaging in learning. 24 It is obvious that students who have better online self-efficacy feel relatively comfortable expressing themselves in writing. 43 It has been reported that misinterpreted text communication is common in online learning.…”
Section: Discussionmentioning
confidence: 99%
“… 5 The ability to use technology is influenced by age and different generational groups have various capabilities. 7 The current students of the medical and health sciences belong to generations that socially interact using technology to ensure connectedness. 8 To optimise the efficacy of learning and facilitate online learning, it is important to understand each generation’s way of learning and teaching.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Na chwilę obecną, w najbardziej optymistycznych prognozach, stanowią one maksymalnie 10% składu pracowniczego (Wasiluk & Tomaszuk, 2022, s. 61-62). Podobne proporcje obserwuje się w innych krajach europejskich oraz w Stanach Zjednoczonych (Ersoz & Demir Askeroğlu, 2019). Niemniej jednak, z biegiem lat, możemy oczekiwać systematycznego wzrostu liczebności tego pokolenia na rynku pracy, jak również rosnącej roli, jaką będą pełnić.…”
Section: Wprowadzenieunclassified